Integration, decentralization, taxation, and revenue sharing: Good governance, sustainable fiscal policy and poverty reduction as peace-keeping strategies ; Paper prepared for the GTZ-Director's Seminar for the General Secretariat of the EAC on Tax Harmonization and Regional Integration, Arusha/Tanzania, April 23/24, 2008 - Hans-Georg Petersen (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2008)
The paper tries to shed some light on the problems of centralization and decentralization within an economic union and the federal member states. Integration and decentralization are not opposite policy strategies but both meaningful if the single public goods and services supplies are analyzed in more detail. Both strategies doubtlessly have advantages, which can be realized if the manifold possibilities are combined in an efficient approach of good governance. Best practice approaches in inter- or supra-national integration, fiscal federalism and taxation do exist and have to be successfully implemented. Obviously such a modern fiscal policy has to be accompanied by an appropriate monetary policy, which in an economic union has to be carried out by an independent central bank as one of the necessary countervailing powers in a democratic setting. A modern fiscal policy strategy efficiently controls budget deficits, which naturally have to be limited to finance reliable public investments. Such strategy has to be safeguarded through modern methods of budgeting and fiscal planning. Modern public management with a clear code of conduct for the government officials ensures corruption free administration.
urn:nbn:de:kobv:517-opus-27367
Keywords: H7; F5; F15; H8; N4; O2; H2; 330; Centralization; decentralization; ethnic differences; fiscal federalism; fiscal planning; good governance; harmonization; integration; nation building; revenue sharing; sustainable fiscal policy; tax reform; Wirtschaftsintegration; Finanzföderalismus; Finanzausgleich; Finanzpolitik; Nachhaltigkeit; Good Governance; Theorie; Deutschland